Microbiota-bone axis in ageing-related bone diseases - Fu, Liangxuan; Zhang, Peilin; Wang, Yicheng; Liu, Xiaonan (Frontiers in Endocrinology, 2024)
Bone homeostasis in physiology depends on the balance between bone formation and resorption, and in pathology, this homeostasis is susceptible to disruption by different influences, especially under ageing condition. Gut microbiota has been recognized as a crucial factor in regulating host health. Numerous studies have demonstrated a significant association between gut microbiota and bone metabolism through host-microbiota crosstalk, and gut microbiota is even an important factor in the pathogenesis of bone metabolism-related diseases that cannot be ignored. This review explores the interplay between gut microbiota and bone metabolism, focusing on the roles of gut microbiota in bone ageing and aging-related bone diseases, including osteoporosis, fragility fracture repair, osteoarthritis, and spinal degeneration from different perspectives. The impact of gut microbiota on bone metabolism during aging through modification of endocrinology system, immune system and gut microbiota metabolites are summarized, facilitating a better grasp of the pathogenesis of agingrelated bone metabolic diseases. This review offers innovative insights into targeting the gut microbiota for the treatment of bone ageing-related diseases as a clinical therapeutic strategy.